POVERTY AND ADOLESCENT DROPOUTS: A CASE STUDY OF THE RATIONALITY OF SURVIVAL OF RURAL COMMUNITIES - Zahro Tussita; Chelsea Aulia Diswansyah; Aatinaa Minladunka Rohmah (Al Madjid : jurnal Pendidikan Islam, 2026)
This study examines the paradox of adolescents dropping out of formal education in Baros Village, Brebes Regency, where short-term economic pressures perpetuate structural poverty and hinder upward social mobility. The study aims to unravel the local sociocultural dynamics mediating the decision to drop out of school, filling a gap in the existing literature that has focused too heavily on macroeconomic factors. Using a qualitative case-study design, the research involved eight key informants through in-depth interviews, participant observation, and document analysis. Data were analyzed using the Miles, Huberman, and Saldana interactive model to ensure validity through source triangulation. Findings reveal three typologies of vulnerability: sudden shocks, chronic structural poverty, and dependence on the informal economy. The decision to drop out of school is driven by the high opportunity costs of adolescent labor, the burden of hidden costs, and a low perceived return on investment in education. Parents construct education as a "tertiary luxury" and children as "strategic economic assets," creating what is termed "contextual survival rationality." This phenomenon indicates that dropping out of school is not merely a passive consequence of poverty but rather a calculated adaptive strategy for survival. Consequently, the cycle of intergenerational poverty persists because education is viewed as a threat to household economic stability rather than a way out, thus requiring policy interventions that are not merely charitable but also structural and aimed at changing families' perceptions of economic values.